Valsalva Retinopathy Presenting as Subretinal Hemorrhage - Lívia Conci; Eliza Pereira; Samia Navajas; Epitacio Silva Neto; Sérgio Pimentel; Leandro Zacharias (Case Reports in Ophthalmological Medicine)
Purpose. To describe a case of subretinal hemorrhage due to the Valsalva maneuver in a patient with no underlying chorioretinal disease. Methods. History and clinical examination, optical coherence tomography (OCT), fluorescein, and indocyanine green angiography. Results. We report a case of a 35-year-old man with a 4-day history of central vision loss in the left eye (OS) after a vomiting episode. His best-corrected visual acuity was 20/200 in OS. Fundus examination revealed a subretinal hemorrhage in the posterior pole, associated with a small preretinal hemorrhage in the superotemporal arcade. OCT confirmed the presence of a thick submacular hemorrhage and a focal hemorrhage beneath the inner limiting membrane along the superotemporal arcade. The patient was submitted to pars plana vitrectomy (PPV), subretinal injection of tissue plasminogen activator (tPA), and air tamponade on the following day. Most of the submacular hemorrhage was displaced, resulting in a satisfactory visual outcome (BCVA=20/30 after 1 month of surgery). Fluorescein and indocyanine green angiography excluded conditions such as retinal arterial macroaneurysm, polypoidal chorioretinopathy, and choroidal neovascularization. Conclusion. Although rare, Valsalva retinopathy may present with submacular hemorrhage in a patient with no underlying chorioretinal disease. PPV and subretinal tPA injection may provide a good visual outcome.